SCREENING SINGLE RESISTANCE OF Eleusine indica ON OIL PALM PLANTATION IN PADANG LAWAS AND TAPANULI SELATAN REGENCY INDONESIA - Koko Tampubolon; Edison Purba (Jurnal Natural, 2018)
Abstract: Eleusine indica population from several estates in Padang Lawas and Tapanuli Selatan Regency, Sumatera Utara Indonesia has never been reported to be resistant to glyphosate herbicide. This study aims at distribution mapping and resistance classification of Eleusine indica glyphosate-resistant populations from several estates in Padang Lawas and Tapanuli Selatan Regency, Sumatera Utara. This research was conducted at Weed Research Center of the Faculty of Agriculture, Universitas Sumatera Utara from October 2016 to August 2017. This research used glyphosate at the recommended rate of 720 g ai ha-1 and three replications. Population ESU0 (from Politeknik Negeri Medan Ball Field) as a comparison. Data analysis using t-test at the level of 5% with IBM SPSS Statistics 20 software. The results showed 22 populations in Padang Lawas Regency have 8 populations classified as glyphosate-resistant (36.36%), 8 populations classified as developed-resistant (36.36%), and 6 populations classified as glyphosate-susceptible (27.27%). While from 6 populations in Tapanuli Selatan Regency have 5 populations classified as glyphosate-resistant (83.33%), 1 populations classified as developed-resistant (16.67%), and 0 populations classified as glyphosate-susceptible (0%). Keywords: glyphosate, goosegrass, oil palm plantation, resistance.